Vertebral Artery Compression Syndrome - Li, Qi; Xie, Peng; Yang, Wen-Song; Yan, Bernard; Davis, Stephen; Caplan, Louis R. (Frontiers in Neurology, 2019)
Objective: We aim to propose the term “vertebral artery compression syndrome” to describe a group of patients with a variety of clinical symptoms caused by vertebral artery compression of the medulla or spinal cord. Methods: We conducted the prospective case study in a university teaching hospital. Eleven patients who fulfilled the diagnostic criteria of vertebral artery compression syndrome and 22 age- and sex- matched controls were recruited. Clinical presentation and radiological findings of patients with vertebral artery compression syndrome were assessed and recorded. The basilar artery diameter was measured at the midpons level on T2 weighted MR images and compared between both groups. Results: Medullary compression was observed in 10 of 11 patients.The most common clinical presentation is dizziness, vertigo, imbalance or ataxia followed by limb weakness. Cervical spinal cord compression was observed in one patient who presented with neck pain and left leg weakness. The mean basilar artery diameter was similar between patients and controls (3.95±0.41 mm vs 3.81±0.43mm). Conclusions: Vertebral artery compression of medulla and spinal cord may cause various clinical symptoms even in patients without basilar artery dolichoectasia. Future studies are needed to further clarify the prevalence, natural history and treatment of this condition.